EXPERIMENTAL ASPECTS OF TORSIONAL SPRINGBACK IN RECTANGULAR STRIPS. - Dwivedi J.P.; Sarkar P.K.; Ram. S.; Talukder N.K.Das; Singh A.N. (My University, 2025)
An experimental study of springback was done to establish the relationship between springback and length, breadth and thickness while the strip is subjected to torsional loading. Two different materials viz, mild steel and aluminum, were tested and it has been shown in this work that springback increases as the material stiffness (elastic modulus) decreases. It was also observed that the springback percentage kept on increasing uniformly with length of strip while it decreased with thickness increment and had very little effect of width. Thus it is depicted here that torsional springback can be attributed to the configuration and material property. In this paper, method of experimentation and deriving the results in the direction of our predictions are presented. It is also shown how one can use these results independently by normalizing the measured quantities for design.